Low historical nitrogen deposition effect on carbon sequestration in the boreal zone. Issue 12 (18th December 2015) - Fleischer, K.; Wårlind, D.; van der Molen, M. K.; Rebel, K. T.; Arneth, A.; Erisman, J. W.; Wassen, M. J.; Smith, B.; Gough, C. M.; Margolis, H. A.; Cescatti, A.; Montagnani, L.; et al.
Abstract: Nitrogen (N) cycle dynamics and N deposition play an important role in determining the terrestrial biosphere's carbon (C) balance. We assess global and biome‐specific N deposition effects on C sequestration rates with the dynamic global vegetation model LPJ‐GUESS. Modeled CN interactions are evaluated by comparing predictions of the C and CN version of the model with direct observations of C fluxes from 68 forest FLUXNET sites. N limitation on C uptake reduced overestimation of gross primary productivity for boreal evergreen needleleaf forests from 56% to 18%, presenting the greatest improvement among forest types. Relative N deposition effects on C sequestration (dC/dN) in boreal, temperate, and tropical sites ranged from 17 to 26 kg C kg N −1 when modeled at site scale and were reduced to 12–22 kg C kg N −1 at global scale. We find that 19% of the recent (1990–2007) and 24% of the historical global C sink (1900–2006) was driven by N deposition effects. While boreal forests exhibit highest dC/dN, their N deposition‐induced C sink was relatively low and is suspected to stay low in the future as no major changes in N deposition rates are expected in the boreal zone. N deposition induced a greater C sink in temperate and tropical forests, while predicted C fluxes and N‐induced C sink response in tropical forests were associated with greatest uncertainties. Future work should be directed at improving the ability of LPJ‐GUESS and other process‐based ecosystem models to reproduce C cycle dynamics in the tropics, facilitated by more benchmarking data sets. Furthermore, efforts should aim to improve understanding and model representations of N availability (e.g., N fixation and organic N uptake), N limitation, P cycle dynamics, and effects of anthropogenic land use and land cover changes. Key Points: N cycle dynamics in LPJ‐GUESS improve predictions mainly in boreal forests Low absolute effect of N deposition on C sequestration in boreal forests N deposition contributes 19% to recent and 24% to historical land C sink